2018
DOI: 10.1111/joor.12679
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of curcumin in managing acute inflammation pain on the post‐surgical removal of impacted third molars patients: A randomised controlled trial

Abstract: Curcumin is a turmeric-contained active ingredient that has been proven to be effective in treating pain and inflammation due to its analgesic as well as anti-inflammation potential. Odontectomy, on the other hand, has been well known for its post-procedure acute inflammation pain. The aim of the current study was to evaluate the efficacy of curcuminoid in treating acute inflammation post-operative pain in the post-surgical removal of impacted third molars patients. Ninety (44 males; 46 females) participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 40 publications
0
58
0
2
Order By: Relevance
“…Together, these findings suggest that curcumin may protect chondrocytes against IL‐1β‐induced apoptosis. Numerous clinical studies have demonstrated the potentially beneficial effects of curcumin for treating chronic inflammation (Maulina et al, 2018; Panahi et al, 2014). Curcumin increased bone mineral density in postmenopausal women with osteoporosis and reduced pain‐related symptoms in patients with osteoarthritis (Haroyan et al, 2018; Khanizadeh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Together, these findings suggest that curcumin may protect chondrocytes against IL‐1β‐induced apoptosis. Numerous clinical studies have demonstrated the potentially beneficial effects of curcumin for treating chronic inflammation (Maulina et al, 2018; Panahi et al, 2014). Curcumin increased bone mineral density in postmenopausal women with osteoporosis and reduced pain‐related symptoms in patients with osteoarthritis (Haroyan et al, 2018; Khanizadeh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Other investigations, demonstrated that the use of non-steroidal anti-in ammatory drugs can prevent the anesthesia and surgery-associated memory de cits probably via their pain-alleviating effects (Shen et al 2013;Kawano et al 2014). In the same perspective, curcumin, an active ingredient of plant Curcuma longa, is apparently effective in treating POP related to GA and surgery in human (Agarwal et al 2011;Maulina et al 2018), and in mice (Sahbaie et al 2014). As well as suppressing of neuro-in ammatory activation associated with neurodegenerative diseases (Sundaram et al 2017), and preventing anesthetics exposure-induced POCD in mice (Ji et al 2015;Wu et al 2017).…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, the Curcumin also presented a favorable tissue response at the final period of 63 days. This can be attributed to the fact that, as described above, the Curcumin is able to regulate an amount of transcription factors, cytokines, kinases, adhesion molecules, and enzymes related to inflammation process [29].…”
Section: Discussionmentioning
confidence: 98%